Clinical characteristics of hospitalized children with bronchiolitis before and after the COVID-19 pandemic: a single-center study - Amina Saračević; Amela Pašić; Nijaz Tihić; Azra Lukavačkić; Amila Huremović; Džana Kavazović (Medicinski glasnik, 2025)
ABSTRACT Aim: Acute respiratory infections caused by viral pathogens are the most common reason for hospitalization of children. Annually, 150 million infants worldwide are diagnosed with bronchiolitis, and 2-3% of them are hospitalized. This study aimed to compare bronchiolitis severity before and after the COVID-19 pandemic. Methods: This retrospective study was conducted at the Department of Pulmonology, Paediatric Clinic, Clinical Centre University of Tuzla, covering the period from November 1st, 2018, to April th 30, 2019 (pre-COVID period) and November 1st, 2023, to April 30th, 2024 (post-COVID period). A total 129 children under the age of 2 years were involved. Results: No significant differences in the age, body mass, comorbidities, duration of hospitalization, use of oxygen therapy, and mechanical ventilation was found. There was a significant reduction in antibiotic in the post-COVID group (p=0.0173), and a significant increase in the use of aminophylline and inhalation therapy drugs in the post-COVID group. There was a significantly higher number of isolated respiratory syncytial virus (RSV) cases in the post-COVID group, 32 (42.7%). prevalence of fully vaccinated children was significantly higher in the pre-COVID period compared to the post-COVID period, 34 (74.4%?) and 29 (45.3%), respectively. Conclusion: This study reveals a significant increase in the severity of bronchiolitis and an increase in RSV cases after the COVID-19 pandemic. Keywords: anti-bacterial agents,coinfection, oxygen inhalation therapy,respiratory syncytial virus infections, vaccination
Keywords: anti-bacterial agents; coinfection; oxygen inhalation therapy; respiratory syncytial virus infections; vaccination